(untitled) - Belitz, H. D. (Berlin, Germany, 1999)
Logically organized according to food constituents and commodities, this updated manual seeks to provide students and researchers in food science or agricultural chemistry with a useful textbook. There are tables for easy reference and a comprehensive subject index.
Hóa học thực phẩm,Enzyme thực phẩm chuyên sâu,Enzym thực phẩm
Keywords: Food,Thực phẩm; Analysis,Phân tích